2023
DOI: 10.1016/j.hemonc.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Heme Levels During Acute Vaso-occlusive Crisis in Sickle Cell Anemia

Abstract: Objective/Background: Sickle cell anemia (SCA) is associated with increased levels of extracellular heme, which is a key mediator of inflammation in this condition. Despite abundant evidence supporting this concept in cell and animal models, few studies addressed the association between heme levels and the development and severity of acute vasoocclusive crises (VOC) in humans. Methods: A cross-sectional study was conducted in patients with acute VOC. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These interesting results have led to a clinical trial of hemopexin in adults with SCD 25 . Associated with these results, Cardoso et al reported that total extracellular heme levels, both plasma and serum, are correlated with the difference of hemoglobin between admission and convalescence and with SCD severity estimated by composite score 26 . Heme levels were neither associated with VOC severity or hemostasis activation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These interesting results have led to a clinical trial of hemopexin in adults with SCD 25 . Associated with these results, Cardoso et al reported that total extracellular heme levels, both plasma and serum, are correlated with the difference of hemoglobin between admission and convalescence and with SCD severity estimated by composite score 26 . Heme levels were neither associated with VOC severity or hemostasis activation.…”
Section: Discussionmentioning
confidence: 88%
“…Heme levels were neither associated with VOC severity or hemostasis activation. Moreover VOC is not characterized by significant increases in total extracellular heme levels 26 .…”
Section: Discussionmentioning
confidence: 97%
“…No data are available on differences between these porphyrins comparing plasma and serum. However, there are data for heme showing higher concentrations in serum, even though the levels of both matrices are correlating 18 . We assume that this applies also to CPs, as these molecules share the porphyrin structure.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation activation is a hallmark of both COVID-19 20 and of conditions associated with high levels of extracellular heme, HPX consumption, and HO-1 induction. 21 23 Whether the heme/HPX/HO-1 pathway is associated with coagulation activation in COVID-19 has not been explored.…”
Section: Introductionmentioning
confidence: 99%